Teachers' Innovative Work Behavior as a Function of Self-Efficacy, Burnout, and Irrational Beliefs: A Structural Equation Model - Angelos Gkontelos; Julie Vaiopoulou; Dimitrios Stamovlasis (MDPI AG, 2023)
Teachers' innovative work behavior (TIWB) is crucial in the contemporary demanding educational environments for overcoming any commonplace issues and to ensure sustainability and development. It refers to a process in which the employee tries to create new ideas, adopt them, apply them in the school context, and then communicate them to other members of the organization in order to achieve a communal benefit. Among a plethora of factors that could influence such behavior, self-efficacy, burnout, and irrational beliefs have been proposed as potential covariates. In the present study, the associations of the above constructs with TIWB are concomitantly investigated by employing structural equation modeling (SEM). Data were taken from the participation of in-service teachers (N = 964) in primary education via self-reported questionnaires. The proposed SEM model exhibited a satisfactory goodness-of-fit to the empirical data, highlighting the direct effects of the independent variables on TIWB, while mediation analysis showed that irrational beliefs and burnout act also as mediators between self-efficacy and innovative work behavior. The findings are in line with previous reports and are interpretable in the context of modern theories, while a discussion on theoretical and practical implications along with emerging ideas and perspectives for further research is provided.